2010
DOI: 10.1016/j.neuint.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Time course of upregulation of inflammatory mediators in the hemorrhagic brain in rats: Correlation with brain edema

Abstract: Intracerebral hemorrhage (ICH) can cause secondary brain damage through inflammation-related pathways. Thrombin and one of its receptors, protease activated receptor-1 (PAR-1); matrix metalloproteinase (MMP)-9; and aquaporin (AQP)-4 are stroke-related inflammatory mediators that have been implicated in ICH pathology. To further characterize the inflammatory response after ICH, we studied the temporal profile of the expression of these inflammatory mediators and assessed their potential correlation with brain e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…25 In ICH animal models, several studies showed that elevated levels of MMP-9 lead to BBB breakdown and brain edema. [12][13][14][15] It was recently demonstrated that MMP-9 and MMP-3 jointly contributed to blood-induced lesions and neuronal cell death. 16,17 In previous clinical studies, MMP-9 levels significantly correlated with PHE volume in the first 24 hours after symptom onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 In ICH animal models, several studies showed that elevated levels of MMP-9 lead to BBB breakdown and brain edema. [12][13][14][15] It was recently demonstrated that MMP-9 and MMP-3 jointly contributed to blood-induced lesions and neuronal cell death. 16,17 In previous clinical studies, MMP-9 levels significantly correlated with PHE volume in the first 24 hours after symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Matrix metalloproteinase (MMP)-3 and MMP-9, [8][9][10] as well as growth factors (GFs) such as vascular endothelial growth factor (VEGF) and Angiopoietin-1 (Ang-1), 11 are expressed in abnormally high concentrations in brain and peripheral blood in ICH patients. In ICH animal models, elevated MMP-9 and MMP-3 contribute to blood-brain barrier (BBB) disruption, 12,13 brain edema, 14,15 and neuronal cell death. 16,17 Other animal models of ICH and brain injury showed that alteration of VEGF and Ang-1 was related to increased BBB permeability and brain edema.…”
mentioning
confidence: 99%
“…18 Thrombin and proteinase-activated receptor-1 are upregulated starting at 3 hours and peaking 2 days after ICH in animal models. 25 Therapeutically, it may be possible to separate the beneficial and adverse effects of thrombin because they occur in different compartments and during different time frames or have different mechanisms. The beneficial effects of thrombin occur relatively soon after hemorrhage and are mostly vascular.…”
Section: Coagulationmentioning
confidence: 99%
“…Previous studies (Sharp et al, 2008;Wu et al, 2010) suggest that thrombin can cause a secondary injury by recruiting inflammatory cells to form an excessive inflammatory reaction. In the early inflammatory reaction, there are two major cellular components: the peripheral blood-derived exogenous neutrophilic granulocytes and neutrophils and the central nervous tissue-derived endogenous microglia.…”
Section: Introductionmentioning
confidence: 99%